An Integrated Rice Quality Control Application in Central Java using the Feature-Driven Development (FDD) Method - Diovianto Putra Rakhmadani; Gita Fadila Ftiriana; I Putu Restu Indriawan; Tsabitatul Iffah (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) STMIK Global Informatika MDP, 2022)
Rice is the main food commodity in Indonesia. With a consumption level in 2021 of 31.9 million tons, an increase of 351.71 thousand tons compared to the previous year. However, this increase in the amount of production does not increase with an increase in rice quality. Based on BPS data in 2021, the import of quality rice is 41,800 tons. This is because there are still seekers of quality rice as the main food ingredient. To achieve rice self-sufficiency in Central Java Province and produce good quality rice, monitoring must be carried out starting from upstream (farmers) to downstream (distributors) of rice. The Integrated Rice Quality Control Application is designed to answer these problems. With the development of the Feature-Driven Development (FDD) software development method, the application can ensure the quality of rice can be maintained properly. The system design is carried out with an approach that aims to make it easier for its users. The design of this application is also proven to be acceptable for its users with the level of SUS testing with an average score of 70.95 which has been designed in the good category and can be implemented.